(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In recent years, air pollution has become a pressing issue at both global and national levels. This article examines the dynamics of atmospheric pollutant emissions in Uzbekistan during 2020–2024 from the perspective of the interrelationship between economic activity, human well-being, and environmental policy. The study is based on national statistical data and highlights the decline during the pandemic period as well as the subsequent recovery processes. The results indicate a 6.2% reduction in total emissions, confirming the effectiveness of environmental policy and technological modernization. The paper also analyzes regional disparities, sectoral factors, and the growth of environmental awareness, and proposes practical recommendations for the transition to a green economy.